Development and Validation of a Nomogram for Predicting Radiation-Induced Temporal Lobe Injury in Nasopharyngeal Carcinoma - Guan, Wenqiang; Xie, Kang; Fan, Yixin; Lin, Stefan; Huang, Rui; Tang, Qianlong; Chen, Ailin; Song, Yanqiong; Lang, Jinyi; Zhang, Peng (Frontiers in Oncology, 2020)
Background: Radiation-induced temporal lobe injury (TLI) is one of the most serious late complications after definitive radiotherapy of nasopharyngeal carcinoma (NPC). We aimed to develop and validate a nomogram for prediction on TLI in patients with NPC. Methods: The prediction model was developed based on a primary cohort that consisted of 194 patients. The data was gathered from January 2008 to December 2010. Clinical factors associated with TLI and Dose-volume histograms for 388 evaluable temporal lobes were analyzed. Multivariable logistic regression analysis was used to develop the predicting model, which was conducted by R software. The performance of the nomogram was assessed with calibration and discrimination. An external validation cohort contained 197 patients from January 2011 to December 2013. Results: Among the 391 patients, 77 patients developed TLI. Predictors contained in the prediction nomogram included Dmax (the maximum point dose) of temporal lobe, D1cc (the maximum dose delivered to a volume of 1 mL), T stage, and neutrophil-to-lymphocyte ratios (NLR). The Internal validation showed good discrimination, with a C-index of 0.847 [95%CI 0.800 to 0.893], and good calibration. Application of the nomogram in the external validation cohort still obtained good discrimination (C-index, 0.811 [95% CI, 0.751 to 0.870]) and acceptable calibration. Conclusions: This study presents a nomogram that incorporates Dmax, D1cc, T stage, and NLR, which may be conveniently used to facilitate the individualized prediction of TLI in patients with NPC.